Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.4236/ojped.2022.125074
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Accidents in Under-Fives: Epidemiology, Diagnosis, Management, and Outcomes

Abstract: Introduction: Domestic accidents are a public health problem, and under-fives are particularly affected. We report these accidents' epidemiology, diagnosis, management, and outcomes through this study. Patients and Methods: We conducted a prospective descriptive study for four months in the Albert Royer National Children's Hospital Center pediatric surgery department in Dakar, Senegal. Of the 149 cases of domestic accidents, 109 were included in this study. Results: Infants (59.6%) were the most affected, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In regards to overall gender distribution of injuries, we found that males were more involved that females. This pattern of injuries among males and female children have also been reported by other researchers in Africa [4,8,12,13] and other continents [3,7,15] What is more interesting is the peculiarity of some home accidents among boys and girls. In our study, while girls were significantly more involved in burns injuries, probably, as a result of their participation in domestic chores like cooking, boys on the other hand, were more involved with accidental ingestion of poisonous substances and animal bites, probably as a result of lesser participation in cooking and kitchen chores making them free to explore other parts of their homes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In regards to overall gender distribution of injuries, we found that males were more involved that females. This pattern of injuries among males and female children have also been reported by other researchers in Africa [4,8,12,13] and other continents [3,7,15] What is more interesting is the peculiarity of some home accidents among boys and girls. In our study, while girls were significantly more involved in burns injuries, probably, as a result of their participation in domestic chores like cooking, boys on the other hand, were more involved with accidental ingestion of poisonous substances and animal bites, probably as a result of lesser participation in cooking and kitchen chores making them free to explore other parts of their homes.…”
Section: Discussionsupporting
confidence: 83%
“…The home environment is meant to be a safe environment for children, however, in the presence of physical, chemical and mechanical hazards, children are in danger of injuries at home [2]. These hazards include slippery floors, poor lightening at home, sharp objects, medications, chemicals kept within the reach of children and the presence of animals within the vicinity of the home that cause injuries to humans through their bites [3][4][5]. Common injuries associated with domestic accidents include lacerations, burns, head injuries, intoxication from ingestion of chemicals, drowning and near drowning, fractures, dislocations and animal bites among others [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation